The Implementation of the Innovative “Connecting Knowledge” Intervention to Improve Vulva Hygiene Practices in Cervical Cancer Prevention - Rinda Intan Sari; Anis Ardiyanti; Nella Vallen Ika Puspita; Ni Made Ayu Wulansari (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: The cause of cervical cancer is HPV, the transmission of which stems from poor personal hygiene, particularly inadequate vulvar hygiene. One factor that can influence adolescents to practise self-care, particularly vulvar hygiene, is knowledge and behaviour. A lack of accurate knowledge and information among adolescents regarding reproductive health can lead to a lack of responsibility for their own reproductive health. They feel embarrassed and consider this a taboo subject to discuss; therefore, peer education is effective in influencing behavioural change, encompassing knowledge, attitudes, and skills among adolescents. The aim of this study is to analyse the influence of “Connecting Knowledge” to vulva hygiene practices in cervical cancer prevention. Methods: The research design is a a quasi-experimental pre-test–post-test design without a control group. The sample will be selected using quota sampling, with inclusion criteria comprising third- and fifth-semester nursing students and adolescents aged 12–19 years. Group I consists of 10 third- and fifth-semester students from STIKES Telogorejo in Semarang; Group II comprises 20 individuals; and Group III comprises 40 adolescents from the Karang Ayu sub-district. Quantitative data were managed and analysed using SPSS, using a Paired t-test with a p-value of <0.05. Results and Recommendation: The results of this study show that the majority of respondents were aged 18 and p value <0.05, indicate that connecting knowledge influences adolescents’ knowledge (0.05 and 0.012) and behaviour (0.012 and 0.034) regarding vulvar hygiene in the prevention of cervical cancer. It is recommended that further research should incorporate additional interventions and involve a wider range of stakeholders, thereby providing adolescents with a safe space to look after their health without feeling embarrassed to speak openly. Cervical cancer prevention begins in adolescence and continues into adulthood, and could be incorporated as one of the interventions within comprehensive nursing care.